Persistence of Hepatitis C RNA in Liver Allografts Is Associated with Histologic Progression Independent of Serologic Viral Clearance - M. Ghabril; R. C. Dickson; M. Krishna; R. Lloyd; J. Aranda-Michel; A. Keaveny; R. Satyanarayana; H. Bonatti (Journal of Transplantation)
Background. Hepatitis C virus (HCV) nondetectability in the liver may predict a sustained viral response (SVR) in patients with an end of treatment response. HCV RNA can be detected in liver tissue by in situ hybridization (ISH). Aim. To determine if HCV nondetectability in liver allografts by ISH can predict SVR in patients who cleared virus serologically on treatment. Methods. Twenty five patients with undetectable serum HCV on Interferon/Ribavirin therapy for HCV recurrence post liver transplant (LT) were studied. All had biopsies at 4 months post LT (baseline) and follow up with HCV ISH analysis performed. Results. 10 were ISH positive (group 1); 15 were ISH negative (group 2). Groups 1 and 2 had similar patient, donor, and viral characteristics at LT, as well as treatment duration at the time of the ISH assayed liver biopsy (13±16 versus 10±4 months P = .24). However, group 1 had longer total treatment duration (24±10 versus 14±5 months, P = .001). Eight (80%) group 1 and 9 (60%) group 2 patients achieved SVR. Mean grade and stage (modified Ishak score) were similar at 4 months, however, group 1 had higher grade (3±1.7 versus 1.6±1.3, P = .039) and stage (1.4±1.4 versus 0.5±0.6, P = .084) on the ISH assayed biopsy, after similar post LT intervals (23±10 versus 24±12 months, P = .91). Conclusion. Allograft HCV ISH nondetectability does not predict SVR in treatment responsive HCV recurrence, but is associated with less severe histologic disease.